Innovative proteomic approaches for cancer biomarker discovery. (September 2007) - Faca, Vitor; Krasnoselsky, Alexei; Hanash, Samir
Substantial technological advances in proteomics and related computational science have been made in the past few years. These advances overcome in part the complexity and heterogeneity of the human proteome, permitting quantitative analysis and identification of protein changes associated with tumor development. Here, we discuss some of these advances that are uncovering new cancer biomarkers that have potential to detect cancer at early and curable stages and address remaining challenges.